Informal Employment: Features in the North and South of Russia - Marina A. Terentyeva (Арктика и Север)
The spread of informal employment is relevant for the labor market of the Russian Federation as a whole, and for its regions. The relevance of the research problem is associated with the lack of comparative data on the informal sector of the economy of the territories of the north and south of the Russian Federation. The reason for the growth of employment in the informal sector is associated with the devel-opment of the service sector and digitalization of the economy, increased competition in regional markets, which leads to the growth of flexible forms of employment. The purpose of the study is to assess the scale of employment in the informal sector in the northern and southern regions of Russia using a production approach. The work attempts to identify and assess the economic conditions affecting informal employment in the regions under consideration. The author examined three groups of conditions and selected indicators characterizing these conditions, which formed the basis for the analysis of employment dynamics in the informal sector. Panel data were collected on the basis of Rosstat information for recent years, maintaining comparability of data collection and processing methods. The study provides an assessment of employment in the informal sector for the regions of the south and north of the Russian Federation draws conclusions on the impact of the above groups of economic factors on employment in the informal sector in these regions. The relationship between per capita gross regional product and informal employment is revealed. The practical significance of the study lies in the fact that the results obtained may be in demand when assessing the processes of employment change during the development of strategies and programs for regional development. The prospects for further research are determined by a more in-depth analysis of the degree of influence of the current socio-economic situation on the level of employment in the regions.